A Better Technique for Controlling Torque to Preload Relationship in the Accurate Assembly of Tiny Threaded Bolt Joints - A.B. Bhane (International Journal of Fracture Mechanics and Damage Science, 2024)
Our industrial, commercial, and even civil worlds are made possible by threaded fasteners or connections, which include all types of bolts. They offer an easy way to connect a limitless number of small parts to form large and practical objects like printing presses, cars, airplanes, and buildings. This paper describes the ways to determine torque to preload relationship in threaded connection and finalizing the optimum torque to be applied. Explains further "why appropriate bolt tension, also known as preload, is essential to an assembled joint's dependability and safety. A summary of the many approaches to producing that preload will be provided. The paper discusses the case study of threaded connection which is non lubricated and difficult to use the conventional methods to determine the torque to preload relationship due to its geometry.
Keywords: Bolted joints; Friction; K-factor; Minitab; Torque-tension relationship; preload